Industrial market structure and economic performance - Scherer, F. M. (Chicago : Rand McNally College Pub. Co., 1980)
The book provides a systematic presentation of the economic field of industrial organization, which is concerned with how productive activities are brought into harmony with the demand for goods and services through an organizing mechanism, such as a free market, and how variations and imperfections in the organizing mechanism affect the successful satisfying of an economy's wants. Of the three market mechanisms (tradition, central planning, and free markets), the field of industrial organization deals primarily with the market system approach. This book primarily emphasizes the manufacturing and mineral extraction sectors of industrialized economies, with less discussion of wholesale and retail distribution, services, transportation, and public utilities. Beginning with a discussion of the welfare economics of competition and monopoly, the structure of industries in the U.S. and abroad and their determinants are described, including motives for mergers and their effects. Extended analysis of pricing, product policy, and technological innovation then follows. Antitrust, price fixing, related restraints, structural monopolies, regulation, and price discrimination are examined, as are the complex policies governing pricing relationships between vertically linked firms. The role of advertising in product differentiation and the roles of market structure and product variety are identified. Innovation, patents, and their relation to market structure are explored. Overall, this analysis seeks to identify attributes or variables that influence economic performance and to build theories about the links between these attributes and end performance.
Includes index
Includes bibliographical references and indexes.
II 16/01/2019
Loans
Keywords: Industrial organization (Economic theory); Industrial policy